Blue Ocean Strategy: Review of Applications at Nature Elementary School Purwakarta - Muhamad Taufik Bintang Kejora; Diding Nurdin; Eka Prihatin (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study aims to investigate and describe the application of the blue ocean strategy (BOS) in the Nature Elementary School Purwakarta. This research is a qualitative description model. Data collection is done through interviews, documentation, and observation. Respondents involved foundation managers, supervisors, school principals, teachers, parents, students, and community leaders who understand the development of education. Data were analyzed using triangulation techniques. The results showed that the Purwakarta nature elementary school was successful in implementing the blue ocean strategy through the creation of innovation, differentiation and quality improvement through the 4 steps of BOS Eliminate, Reduce, Raise, Create (ERRC). Philosophy, vision and mission, curriculum development, flagship programs, improvement of infrastructure, the use of technology and the development of human resources are key components that will enable the school to create its own blue ocean space. Another finding is that institutions without uniqueness and superiority tend to make them take pseudo advantages which make them just imitate and eventually get tired and give up in competition. So it is important to make blue ocean as a tool for educational organizations to be at an advantage without competition by implementing blue ocean strategy scientific procedures that have proven successful in business, industry and also education.